Gender Differences In Pornography-Viewing-Disorder (IPD) - Mohd Shahrul Kamaruddin; Aini Azeqa Ma’rof; Lin, Chin Chew (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2023)
The rapidly increasing sophistication of technology has allowed users around the world to access a wide variety of data and content on the internet, including pornographic and sexual videos. These pornographic videos that are readily available on the internet are making the minds of young people and adults, that is, regardless of gender increasingly polluted with imaginations and fillings that corrupt their morals. Thus, these studies aim to determine the differences between gender on pornography motivation and sexual arousal and gratification in the tendencies toward Pornography-Viewing-Disorder (IPD). Quantitative research with convenience sampling was used in this study and there was a total of 202 people answered the distributed google form. This study revealed that sexual arousal and seeking pleasure while viewing online pornography are significant factors in the use of online pornography among online pornography users. The implication is also discussed in this study.